2005
DOI: 10.1007/s10450-005-5976-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gas-Solid Heat Transfer on Rapid PSA

Abstract: A simple analytical model of a Differential Pressure Swing Adsorption (DPSA) process on a single adsorbent particle was used to evaluate the effects of gas-solid heat transfer resistance on the cyclic working capacity of the particle. The commonly used assumption of instantaneous thermal equilibrium between the gas and the adsorbent inside an adsorber may not be valid when the gas flow rates are low, the adsorption kinetics is relatively fast, and the PSA cycle times are small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Using the Ultra-rapid piston driven PSA, the total cycle time was less than 5 seconds (its adsorption/desorption cycles resemble the expansion and compression of an internal combustion engine). Under such conditions, the mathematical models used to simulate normal PSA processes may not work [210,217]: mass and energy transfer description using simplifications like LDF (linear driving force) are not applicable. There are also some particularities related to RPSA that could be overcome with the utilization of specialized devices.…”
Section: Advances In Process Engineeringmentioning
confidence: 99%
“…Using the Ultra-rapid piston driven PSA, the total cycle time was less than 5 seconds (its adsorption/desorption cycles resemble the expansion and compression of an internal combustion engine). Under such conditions, the mathematical models used to simulate normal PSA processes may not work [210,217]: mass and energy transfer description using simplifications like LDF (linear driving force) are not applicable. There are also some particularities related to RPSA that could be overcome with the utilization of specialized devices.…”
Section: Advances In Process Engineeringmentioning
confidence: 99%
“…28 In addition, the simulation ignores the potentially negative influence of finite heat transfer resistance between the gas and the solid phases on the performance of a rapid PSA cycle by assuming isothermal operation. 7 The present work experimentally demonstrates that the BSF of a rapid Skarstrom-like PSA cycle for production of ∼90% O 2 A PSA cycle was chosen for this study because a PSA mode of MOC design may have several practical advantages over a VSA or a PVSA design: (a) direct production of a compressed stream of O 2 product gas, which provides a good driving force to overcome the column pressure drop during steps such as back purge and pressurization with product gas, particularly when small particle sizes are used, and faster execution of these steps are needed, and (b) elimination of the need for a vacuum pump required by a VSA or a PVSA system which can be bulky and a potential source of system leakage. A PVSA system requires a compressor as well as a vacuum pump which complicates system maintenance.…”
Section: ' Rapid Psa Cycle Oxygen Concentratormentioning
confidence: 99%
“…The limiting rate was a strong function of k. 6 A nonisothermal extension of the model, where the effect of a finite gasÀsolid heat transfer coefficient (h) on the performance of a rapid cycle was investigated, showed that the relative efficiency of adsorbate removal by the nonisothermal process relative to the isothermal performance decreased substantially at smaller cycle times. 7 Adsorbent particles of small diameter (d p ) are deliberately used in a rapid PSA cycle in order to decrease the abovementioned kinetic resistances. The transfer coefficients k and h are typically proportional to d p À2 and d p À1 , respectively, in the absence of axial dispersion.…”
Section: ' Introductionmentioning
confidence: 99%
“…Compared to the wealth of literature on equilibrium and kinetic parameters for mass transfer, relatively few papers have considered sensitivity to heat transfer parameters 9,21,23,31,[40][41][42][43] . This is partially due to the simplifying assumption made in many studies [2][3][4][5][6][7][8][10][11][12][13][14][15][16][17][24][25][26]30,32,34 to neglect heat transfer and treat the entire bed as isothermal.…”
Section: Axial Dispersion Is a Complex Function Of Flow Conditions Anmentioning
confidence: 99%
“…This assumption is made despite the fact that system-level models of cyclic pressure and temperature-swing-adsorption processes are known to be highly sensitive to temperature variations 20 . Even studies that account for heat transfer rely on assumptions such as adiabatic walls 21,31,41,43 , constant isosteric heat of adsorption 40,42 , or local thermal equilibrium (LTE) 21,29,40,41,43 . Sircar et al 40 evaluated the adiabatic wall assumption and concluded that while the breakthrough time is insensitive to the ambient heat loss, the profile of concentration in the bed depends strongly on this quantity.…”
Section: Axial Dispersion Is a Complex Function Of Flow Conditions Anmentioning
confidence: 99%